Side channel analysis on AAᵝ cryptosystem and a signing scheme based on bivariate function hard problem and discrete logarithm problem - Abd Ghafar, Amir Hamzah (2015)
This study has two main parts. The first part discusses side-channel attack on the AAb cryptosystem. The encryption scheme was introduced in 2012. Hence this attack is aimed to address new rooms for improvements for AAb . Side-channel attack is an attack on the implementation of a cryptosystem by collecting physical data that are leaked by the machines which execute the cryptosystem. The components of side-channel attacks that are used in this study are timing attack and power attack. We mathematically model the attacks and prove the viability of such attacks. Then we provide solutions on how to overcome. The second part of this thesis presents a new digital signing scheme that utilizes the Bivariate Function hard Problem (BFHP) and Discrete Logarithm Problem (DLP) as its underlying mathematical hard problems. BFHP is the same problem used by AAb while DLP is the established hard problem used by one of the first public-key cryptosystem, Diffie-Hellman cryptosystem. We study and analyze this new scheme with respect to its security and performance when compared to other widely-used digital signing schemes.